Characterization of plant growth promoting rhizobacteria and fungi associated with rice, mangrove and effluent contaminated soil - S.M Muthukkaruppan, Sajani Samuel and (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Plant growth promoting rhizobacteria have been identified in influencing the growth and yield of many plants. The effects of PGPR on plant growth can be mediated by direct or indirect mechanisms. In search of efficient PGPR strains with multiple activities, microbial isolates belonging to Bacillus spp, Pseudomonas spp, Azotobacter spp, Azospirillium spp, Phosphobacteria spp, Glucanacetobacter spp Aspergillus niger and Penicillium spp were isolated from different sources (Rice field, Mangroves and Effluent soil) of Cuddalore district. These test isolates were biochemically characterized and screened in vitro for their plant growth promoting traits like production of Indole acetic acid (IAA), ammonia, HCN and catalase production. All the isolates were able to produce IAA. Production of ammonia was commonly detected in all the isolates. All the test isolates were positive for catalase but none of the isolates produced HCN. On the basis of multiple plant growth promoting activities, the isolates were evaluated for their heavy metal tolerance. Among the isolates used on the heavy metals (Iron, Zinc, Lead, Magnesium and Copper), the effluent isolates were more tolerant to heavy metal and more tolerance were seen on iron metal. Tolerance to heavy metals was observed less frequently in Azospirillium spp, Phosphobacteria spp and Glucanacetobacter spp. The isolates could exhibit more than two or three PGP traits, which may promote plant growth directly or indirectly or synergistically. Further rhizobacteria tolerant to multiple heavy metals exhibited a couple of PGP activities.